Online Collaborative Documents as Media Logic: The Mediatization of Risk Response in the Post-pandemic Era - Jiang, Hao; Zhang, Yi; Guo, Wodong; Cheng, Wei; Peng, Jian (Frontiers in Psychology, 2022)
Online collaborative documents (OCDs) have previously been the focus of office efficiency, but today they can be a special approach to risk response in public health and natural disaster situations. Studying the mediatization of the risk response by OCDs can help us understand the interaction between digital technologies, online users, and emotions in a post-pandemic world. A mixed-method design involving online ethnography and focus groups was employed to discuss OCD performance during the 2021 Henan flood. The empirical results indicate that four dimensions of technological affordances (i.e., editability, accessibility, activability, and normability) connected the functional features of the digital platform with users’ potential actions. Risk communication as a contextual element of media exposure and discursive practice provided a participatory and constructive framework for users’ gathering. Therefore, affective ties including anxiety, fear, and encouragement supported the affective publics’ mass deliberation and social mobilization. These findings provide an institutional lens for mediatization research to view OCD as media logic and reveal some methods that can be referred to for risk management and humanistic concerns globally.